Neontological and paleontological congruence in the evolution of Podocarpaceae (coniferales) reproductive morphology - Leslie, Andrew B.; Benson, Roger B. J. (Frontiers in Ecology and Evolution, 2022)
Podocarpaceae are a diverse, primarily tropical conifer family that commonly produce large leaves and highly reduced, fleshy seed cones bearing large seeds. These features may result from relatively recent adaptation to closed-canopy angiosperm forests and bird-mediated seed dispersal, although determining precisely when shifts in leaf and seed cone morphology occurred is difficult due to a sparse fossil record and relatively few surviving deep lineages. Here we compare the fossil record of Podocarpaceae with the results of ancestral state reconstruction using a molecular time-tree. Ancestral state reconstructions suggest that small leaves, small seeds, and multi-seeded cones are ancestral in crown Podocarpaceae, with reduced cones bearing few seeds appearing in the Early Cretaceous and the correlated evolution of large leaves and large seeds occurring from the Late Cretaceous onwards. The exact timing of these shifts based on neontological data alone are poorly constrained, however, and estimates of leaf and seed size are imprecise. The fossil record is largely congruent with these results and provides important data on the range of leaf and seed sizes that were present in Cretaceous Podocarpaceae, as well as more precise constraints on the time by which changes in cone morphology and seed size likely occurred. We suggest in particular that reduced seed cones appeared in the Early Cretaceous and are linked to the contemporaneous diversification of small bodied avialans (birds), with shifts to larger seed sizes occurring after the Cretaceous in association with the spread of closed-canopy angiosperm forests.